The Clinical Spectrum of Inflammatory Bowel Disease Associated With Specific Genetic Syndromes: Two Novel Pediatric Cases and a Systematic Review - Gatti, Simona; Gelzoni, Giulia; Catassi, Giulia N.; Catassi, Carlo (Frontiers in Pediatrics, 2021)
Background and aims: Inflammatory bowel disease (IBD) is a classical polygenic disorder and more rarely has a monogenic origin. Furthermore, IBD can arise in the context of specific genetic syndromes associated with a risk of autoimmune disorders. We aimed to systematically evaluate the prevalence of IBD in specific genetic syndromes and to review the clinical characteristics of the published cases. Methods: According to PRISMA guidelines, studies describing patients with IBD and a genetic syndrome and/or studies indicating the prevalence or incidence of IBD in subjects with a genetic syndrome were included. Results: Forty-six studies describing a total of 67 cases of IBD in 6 genetic syndromes and 2 unpublished cases, from our personal experience, were included in the review. The majority of cases were associated with Turner syndrome (TS) (38 cases), Down syndrome (DS) (18 cases) and Neurofibromatosis type 1 (NF1) (8 cases). Sporadic cases were described in DiGeorge syndrome (2), Kabuki syndrome (2) and Williams syndrome (1). Prevalence of IBD ranged from 0.67% to 4% in TS and from 0.2% to 1.57% in DS. Incidence of IBD was increased in TS and DS compared to the general population. Eight cases of IBD in TS had a severe/lethal course, most of them described before the year 2000. Five IBD cases in DS were particularly severe. Conclusion: evidence of an increased prevalence of IBD is accumulating in TS, DS and NF1. Management of IBD in patients with these genetic conditions should consider the presence of comorbidities and possible drug toxicities.